(untitled) (Revista Sistemas de Producción Agroecológicos, 2020)
In the present project, the calorific value of the cacay shell (Caryodendron orinocense) from the municipality of Villavicencio was evaluated, determining the calorific power of the cacay shell to different samples that were put through to two types of drying and taken to two particle sizes. To do this, cacay shell was collected from a company dedicated to the extraction of the oil from its nut; the impurities were removed, ground and sieved. Then, they were dried by two methods, some samples were exposed to drying by oven for 12 hours and at 102°C, and other samples were dried in the sun for two days with temperatures close to 32°C, natural conditions of the city of Villavicencio, once the samples were prepared, their calorific value was determined by means of a calorimetric pump. Likewise, the energy consumption of each of the pretreatments to which the samples were subjected was estimated in order to establish an energy balance, thus determining which pretreatments are justifiable to optimize their energy performance, having as a result higher calorific value values included between 4189 and 4629 kcal/kg, with significant energy differences between all the treatments compared to the target, finding that the big size particle and oven drying was presented as having the greatest significant difference according to the analysis of the variances (ANOVA), however, it was determined that the big size particle and sun drying, has the most efficient pretreatments, in terms of energy consumption, indicating that a higher calorific value can be reached than other residual biomass.